Afriat's Theorem for Indivisible Goods - Francoise Forges; Vincent Iehlé (Center for Economic Studies and ifo Institute (CESifo), 2013)
We identify a natural counterpart of the standard GARP for demand data in which goods are all indivisible. We show that the new axiom (DARP, for discrete axiom of revealed preference) is necessary and sufficient for the rationalization of the data by a well-behaved utility function. Our results complement the main finding of Polisson and Quah, Am. Econ. J.: Micro. 5(1) p.28-34 (2013), who rather minimally modify the original consumer problem with indivisible goods so that the standard GARP still applies.
Keywords: D11; C81; 330; Afriat's theorem; GARP; indivisible goods; rationalization; revealed preference